Actualization of the Moderation Library as Cultural Literacy Based on Digital Literacy in Islamic Senior High School - Mawidha, Rahma Fajr; Rodliyah, St; Sahlan, Moh (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The purpose of this study was to determine the actualization of the moderation library as a form of cultural literacy at MAN 2 Banyuwnagi. The research methodology uses a qualitative approach and data collection techniques through observation, interviews, and the study of documents and digital literature. Data analysis was done by data reduction, presentation, and conclusion. The actualization of the moderation library in digital literacy-based cultural literacy at MAN 2 Banyuwangi is an effort and means of strengthening culture and literacy for students to broaden their horizons of knowledge about religious diversity, which produces personality and an attitude of moderation, openness, and being able to respect differences. The moderation library is a place for students to develop literacy through GELEM (Madrasa Literacy Movement) activities that are held once every three months, monthly literacy movements that are carried out every fourth Sunday of every month by reading books in the first hour, as well as appreciation for activities supported by the Al-Ghozy Award to increase students' interest in reading, as well as cross-faith moderation library visits included in the moderation camp with the ministry of religion. This embodiment is an icon that religious moderation at MAN 2 Banyuwangi has been running smoothly and well.